Transgressões de Eros: embates entre interdição e desejo em Hilda Furacão - Sousa Junior, Sebastião Soares de (2021)
The research aimed to analyze the work entitled Hilda Furacão, writen by Roberto Drummond, emphasizing the theme of eroticism. George Bataille's (2017) conceptions regarding discontinuity and the transgressive character of the erotic in the search for continuity theory framework are used as theoretical assumptions. To understand the clashes arising from the relationship between interdict and transgression, the research was based on many authors from human sciences, such as Philosophy, History, Anthropology and Literary Theory. According to these theorists, it could be highlighted some issues such as the occurrence of spaces of legitimate and illegitimate sexualities, conflicts between the low and the high social, identity issues in post-modernity, among others. The main guiding questions are as following: how do the clashes between interdiction, desire and transgression occur in the narrative of Hilda Hurricane? What impels, in a context preceding the civil-military coup of 1964, a privileged girl to leave the comfort of a traditional family and assume the identity of a prostitute? Thus, this research aimed to investigate the clashes/dialogues between the practice of interdict, the creation of desire and the transgressive and erotic drive regarding the work Hilda Furacão, written by Roberto Drummond. There are existing theoretical productions on multiple themes and approaches from the work. However, the relevance of the present research is justified by the absence of analysis from the perspective of eroticism. According to the methodological procedure of bibliographic and qualitative research, it is possible to build the hypothesis that, in Drummond's work, the composition of a repressive society generates what constitutes the erotic object of transgression, in a dialogue between opposite moments that can be harmonized with respect to the Bataille’s eroticism.